Unexpected Complications 25 Years after Coil Embolization for Pulmonary Arteriovenous Fistula - So, Clara; Suzuki, Manabu; Iwaki, Yoshinobu; Sugiura, Yuriko; Suzuki, Yudai; Terayama, Yuriko; Iikura, Motoyasu; Izumi, Shinyu; Hojo, Masayuki; Sugiyama, Haruhito (Internal Medicine, 2023)
An 87-year-old woman who had undergone coil embolization 25 years ago for pulmonary arteriovenous fistula, which was diagnosed following repeated cerebral infarction, presented with massive hemoptysis. The coils migrated and were excreted in stool following hemoptysis during long-term follow-up. Although the technical success rate of coil embolization for pulmonary arteriovenous malformations is extremely high, and coil embolization-related complications are rare, little is known about the long-term complications. We herein report the clinical course of our case, review previous reports related to coil migration as a long-term complication, and discuss the associated mechanism.